2015
DOI: 10.1111/zph.12192
|View full text |Cite
|
Sign up to set email alerts
|

The Establishment of the Colombian Integrated Program for Antimicrobial Resistance Surveillance (COIPARS): A Pilot Project on Poultry Farms, Slaughterhouses and Retail Market

Abstract: • Implementation of a National Integrated surveillance antimicrobial resistance program based on public-private partnership.• Description of good practices in building an integrated surveillance program on antimicrobial resistance that could be used by other countries.• Provide information to conduct risk assessment studies on antimicrobial resistance in Colombia to support policy making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 51 publications
0
48
0
8
Order By: Relevance
“…Data from COIPARS (Colombia) show that Campylobacter spp. strains isolated from chicken and subproducts are very resistant to ciprofloxacin (50-97 %); for erythromycin the reported resistance is 48 %, being most strains isolated from meat from supermarkets whereas 83 % of the strains isolated from carcasses at a slaughtering plant were tetracycline resistant (Donado-Godoy et al 2015). It is important to mark that in most of the reported data, Campylobacter is susceptible to gentamicin and contrary to other Gram negative pathogens does not show high multiresistance levels.…”
Section: Phenotypical Resistance To Antimicrobials In C Jejuni and Cmentioning
confidence: 66%
See 1 more Smart Citation
“…Data from COIPARS (Colombia) show that Campylobacter spp. strains isolated from chicken and subproducts are very resistant to ciprofloxacin (50-97 %); for erythromycin the reported resistance is 48 %, being most strains isolated from meat from supermarkets whereas 83 % of the strains isolated from carcasses at a slaughtering plant were tetracycline resistant (Donado-Godoy et al 2015). It is important to mark that in most of the reported data, Campylobacter is susceptible to gentamicin and contrary to other Gram negative pathogens does not show high multiresistance levels.…”
Section: Phenotypical Resistance To Antimicrobials In C Jejuni and Cmentioning
confidence: 66%
“…Most of the European countries, as well as the developed ones and US, Canada and Australia have resistance surveillance programs for zoonotic pathogens, which include Campylobacter isolated from poultry and or poultry meat. In Latin America, Mexico and Colombia (COIPARS) have surveillance programs that include Campylobacter strains isolated from poultry and its products (Donado-Godoy et al 2015).…”
Section: Phenotypical Resistance To Antimicrobials In C Jejuni and Cmentioning
confidence: 99%
“…Tetracycline and erythromycin resistance rates ranged from 55% to 100% and from 45% to 100%, respectively, in the previous studies performed in Turkey (12,13,17). The research in the other countries also demonstrated high rates of resistance to tetracycline and erythromycin (14,16,18,19). Usui et al (14) found that 92% of E. faecium isolates from poultry feces showed resistance to oxytetracycline, 82.8% to enrofloxacin and 79.4% to erythromycin, while 70.9% of E. faecalis isolates showed resistance to erythromycin, 69.2% to oxytetracycline and 17.9% to enrofloxacin, and the authors suggested that antibiotic resistance may be different in different Enterococcus species.…”
Section: Discussionmentioning
confidence: 99%
“…Los aislamientos de Salmonella derivados del proceso productivo en la EI-I correspondieron en su mayoría a S. Heidelberg, un serotipo descrito en estudios internacionales (22) y en Colombia en donde además se le ha demostrado multirresistencia a las drogas (23).…”
Section: Discussionunclassified